1958
DOI: 10.1037/h0042202
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and extinction of the conditioned eyelid response following partial and continuous reinforcement.

Abstract: This article is based on a dissertation submitted to the Graduate College of the State University of Iowa in partial fulfillment of the requirements for the Ph.D. degree. The author is indebted to Kenneth W. Spence who directed the investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

1963
1963
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 15 publications
4
33
1
Order By: Relevance
“…Various manipulations of schedules of partial reinforcement involving CS alone and CS-US paired trials in human eyeblink conditioning have produced three major findings. These results include a significant decrement in acquisition in the partial reinforcement group as compared to the continuous reinforcement group (Reynolds, 1958 ; Ross, 1959 ; Hartman and Grant, 1960 ; Ross and Spence, 1960 ; Runquist, 1963 ; Perry and Moore, 1965 ), a partial reinforcement extinction effect (PREE; Longenecker et al, 1952 ; Perry and Moore, 1965 ; Newman, 1967 ; Leonard, 1975 ), and a null effect of no significant differences in acquisition between partial and continuous reinforcement schedules (Humphreys, 1939 ; Grant et al, 1950 ; Hake and Grant, 1951 ; Grant and Schipper, 1952 ; Moore and Gormezano, 1963 ; Price et al, 1965 ; Foth and Runquist, 1970 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various manipulations of schedules of partial reinforcement involving CS alone and CS-US paired trials in human eyeblink conditioning have produced three major findings. These results include a significant decrement in acquisition in the partial reinforcement group as compared to the continuous reinforcement group (Reynolds, 1958 ; Ross, 1959 ; Hartman and Grant, 1960 ; Ross and Spence, 1960 ; Runquist, 1963 ; Perry and Moore, 1965 ), a partial reinforcement extinction effect (PREE; Longenecker et al, 1952 ; Perry and Moore, 1965 ; Newman, 1967 ; Leonard, 1975 ), and a null effect of no significant differences in acquisition between partial and continuous reinforcement schedules (Humphreys, 1939 ; Grant et al, 1950 ; Hake and Grant, 1951 ; Grant and Schipper, 1952 ; Moore and Gormezano, 1963 ; Price et al, 1965 ; Foth and Runquist, 1970 ).…”
Section: Introductionmentioning
confidence: 99%
“…Group differences in the rate of extinction might be indicative of difficulty changing existing associations, poor attention to changing stimulus conditions, or interference in associative memory (e.g., Berger & Orr, 1983;Bouton, 1991;Grant & Schipper, 1952;Mosley, Bakal, & Pilek, 1974;Reynolds, 1958;Spence & Platt, 1967). Group differences in the rate of extinction might be indicative of difficulty changing existing associations, poor attention to changing stimulus conditions, or interference in associative memory (e.g., Berger & Orr, 1983;Bouton, 1991;Grant & Schipper, 1952;Mosley, Bakal, & Pilek, 1974;Reynolds, 1958;Spence & Platt, 1967).…”
Section: Comparing Preterm and Full-term Learnersmentioning
confidence: 99%
“…Given the similarity between preterm and full-term learner infants on acquisition measures, we then compared these infants' performance during extinction. Group differences in the rate of extinction might be indicative of difficulty changing existing associations, poor attention to changing stimulus conditions, or interference in associative memory (e.g., Berger & Orr, 1983;Bouton, 1991;Grant & Schipper, 1952;Mosley, Bakal, & Pilek, 1974;Reynolds, 1958;Spence & Platt, 1967). A 2 (preterm vs. full-term) x 2 (sessions) x 8 (blocks) repeated-measures ANOVA of percentage CRs from the two learner groups revealed a significant main effect ofblocks, F(7,70) = 2 1 .…”
Section: Comparing Preterm and Full-term Learnersmentioning
confidence: 99%
“…would be more fearful during extinction than partially reinforced groups (67-67 and 33-33). This conclusion is based on a number of studies showing that the acquisition of a classically conditioned response is seriously retarded by partial reinforcement (Pavlov, 1927; Grant 6e Schipper, 1952; Razran, 1955;Reynolds, 1958). Thus, the higher the percentage of shock trials during extinction, the more fear would be present to motivate the running response, if, as Mowrer has hypothesized, this fear generalizes throughout the alley.…”
Section: Speed Across Sectionsmentioning
confidence: 99%
“…The lack of significant results found by the present study might be attributed to the differential effects of partial reinforcement on classical as opposed to instrumental conditioning. It has been shown that the acquisition, and in some cases the resistance to extinction, of a classically conditioned response is seriously retarded by low percentages of reinforcement (Pavlov, 1927;Grant & Schipper, 1952;Razran, 1955;Reynolds, 1958; Lewis, 1950). On the other hand, a number of studies have shown that partial reinforcement leads to greater resistance to extinction (of instrumentally conditioned responses) than continuous reinforcement (Lewis, 1960).…”
Section: Effects Of Partial Reinforcement Upon Resistance To Extinctimentioning
confidence: 99%